Kazimierz Romaniuk : a scholar profile - Wiśniewska, Monika (Instytut Historii Nauki im. Ludwika i Aleksandra Birkenmajerów Polskiej Akademii Nauk, 2019)
The article aims to showcase Polish Roman Catholic Bishop Kazimierz Romaniuk as an academic, biblical scholar, one of the translators of the Millennium Bible and the sole translator of the Warsaw–Praga Bible. He authored numerous monographs, academic studies and other writings devoted to biblical topics and lectured at the Catholic University of Lublin, the Academy of Catholic Theology, the Pontifical Faculty of Theology and the Metropolitan Higher Theological Seminary in Warsaw, of which he became the rector. The study focuses on the course of the scholar’s education and career as well as his academic achievements and significance in the 20th-century Catholic biblical studies in Poland and the international biblical criticism.
Keywords: Kazimierz Romaniuk; theology; Biblical studies; Warsaw–Praga Bible; Academy of Catholic Theology in Warsaw; Metropolitan Higher Theological Seminary in Warsaw